STRATEGI KEKUATAN LOGISTIK UNTUK MENINGKATKAN KINERJA DI SEKTOR INDUSTRI PAKAIAN JADI - Matoati, Rindang; Muslikhah, Rr. Siti; Zahra, Nisa; Azis, Eka Noviani; Palahuddin, Akasyah (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2016)
In modern era, there is a change in human basic needs for apparel that willmake business in fashion industry become interesting dan increasing siginifi cantly. TheÂ growth of apparel industry contributes wealth enhancement of the stakeholders, startingÂ from suppliers, small producers to big producers -such as small medium entreprises toÂ national companies, and distributors. But there are also some obstacles faced by thoseÂ stakeholders that slower their improving performance in Indonesiaâs apparel industryÂ development such as logistics problem, especially in Jabodetabek (Jakarta, Bogor,Â Depok, Tangerang, Bekasi) area. The purposes of this research are: 1) To identify theÂ strengths, weaknesses, opportunity and threat of logistics in apparel industry, 2)ToÂ formulate strategy to advantage the power of logistics as an effort to improve apparelÂ industry performance in Jabodetabek area. This research took place in Jabodetabek,Â Indonesia. SWOT analysis and AHP method were used to analyze the data. The resultsÂ of this research is aimed to provide a right management strategy of logistics to improveÂ apparel industry performance in Jabodetabek.